Analysis of the Effect of the Implementation of Cloud-Based Accounting Information Systems, User Understanding Levels, and Data Quality on the Efficiency of the Audit Process (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The implementation of cloud-based accounting information systems has significantly transformed modern auditing practices. This study examines the influence of cloud-based system implementation, user understanding level, and data quality on the efficiency of the audit process. This study uses a qualitative approach with case studies on organizations that have implemented cloud-based systems. Data was collected through in-depth interviews, direct observations, and documentation of the audit process. The results show that the implementation of cloud-based systems improves audit efficiency by reducing manual tasks and enabling better data integration. User understanding and high data quality are important factors in ensuring reliable audit results. In addition, organizational readiness and integration with advanced technologies such as big data analytics further strengthen the benefits of cloud-based systems in auditing.